A suitable analytical formula for the K shell ionization cross section of carbon and potassium atoms by electron impact - Salim H. Al-Shamma; Muzahim I. Azawi (College of Education for Pure Sciences, 2013)
Abstract: In this study an analytical expression proposed for k shell ionization cross section for two atomic elements C (Z=6) and K (Z=19) due to electron impact had been investigated. This study is based on the analysis of calculated k shell ionization cross section.The proposed analytical expression had been found to fulfill the task of the fitting shape and behavior of the Sbell k ionization cross section database with an acceptable agreement in the values of the cross section at low incident energies.